Beginning IoT projects breadboard-less electronic projects - Bell, Charles (Apress, 2021)
Experiment with building IoT projects without the demanding time or patience required to learn about electronics. This book thoroughly introduces readers of all ages to the world of IoT devices and electronics without getting bogged down by the overly technical aspects or being tied to a specific platform. You'll learn IoT, Arduino, Raspberry Pi from the ground up using the Qwiic and Grove components systems. The book begins with a brief overview of IoT followed by primers for the two most popular platforms; Arduino and Raspberry Pi. There is also a short tutorial on programming each host; Arduino C-like sketches and Python scripts respectfully. Thus, the book also helps you get started with your choice of platform. Next, you'll learn the basics for the Qwiic and Grove component systems. The rest of the book presents a number of projects organized into easy-to-follow chapters that details the goal for the project, the components used, a walk-through of the code, and a challenge section that provides suggestions on how to improve or augment the project. Projects are presented for both the Arduino and Raspberry Pi where possible making each project as versatile as possible. You will: Write Arduino sketches Create Python scripts for the Raspberry Pi Build IoT projects with Arduino and Raspberry Pi Use the Qwiic and Grove component systems Join the electronics and IoT hobby world with almost no experience Host projects data in the cloud using ThingSpeak.